A new endemic species of Willowsia from Florida (USA) and descriptive notes on all New World Willowsia (Collembola: Entomobryidae) - Katz, Aron D. (Zootaxa, 2017)
Four species of Willowsia have been reported from the Americas (W. buski, W. jacobsoni, W. mexicana, and W. nigromaculata), and to date, W. mexicana is the only member of the genus endemic to the New World. Here, Willowsia pyrrhopygia sp. nov. from Florida is described. Like W. mexicana, this new species has a native New World distribution and uninterrupted rib scale type, but can be separated by color pattern and chaetotaxy. Dorsal head chaetotaxy and other descriptive notes are provided to compliment to descriptions for W. buski, W. jacobsoni, W. mexicana, and W. nigromaculata. Comparative morphological analysis also reveals two unique character states among Entomobryinae—the outer maxillary lobe with two (not three) sublobal hairs and the absence of labial triangle seta r—shared only by endemic New World Willowsia and Americabrya, providing preliminary support for their independent evolution from a common New World ancestor.